The neuroanatomy of active hand movement in patients with severe traumatic brain injury: Analysis of functional magnetic resonance imaging data - T. S. Mukhina (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2017)
Objective: to analyze the characteristics of the functional neuroanatomy of movements in severe traumatic brain injury (STBI) patients with varying severity of motor defect versus that in healthy individuals for the study of brain neuroplasticity as a basis of compensation.Patients and methods. Functional magnetic resonance imaging (fMRI, 3T) was used to analyze cerebral hemodynamic changes in 28 patients with STBI during an active right-hand finger tapping task. A control group consisted of 17 healthy individuals. The percentage of representation of individual brain structures involved in movements and volume activation (Vox) was determined in fMRI responses.Results. The patient group showed a tendency for an increased fMRI response diffusion with the emergence of activation zones (the left frontal and parietal regions, as well as the occiptal and temporal regions of the cerebral hemispheres) that are atypical for healthy individuals during motor exercises. This trend is more evident in patients with right-sided hemiparesis.Conclusion. The results of the study clarify the existing ideas about the neurophysiological mechanisms of motor impairment and compensation in traumatic brain injury, which is important for the development and improvement of neurorehabilitation techniques. There is evidence for the hypothesis that the extrapyramidal system may be actively involved in the compensation for post-traumatic musculoskeletal defect, which was earlier proposed by E.V. Sharova et al. (2014).